Pulmonary fungal infections in patients with acute myeloid leukaemia: is it the time to revise the radiological diagnostic criteria?. Issue 6 (11th February 2016) - Maccioni, Francesca; Vetere, Simone; De Felice, Carlo; Al Ansari, Najwa; Micozzi, Alessandra; Gentile, Giuseppe; Foà, Robin; Girmenia, Corrado
Summary: The definition of pulmonary fungal infections (PFI) according to the EORTC‐MSG criteria may lack diagnostic sensitivity due to the possible presentation of PFI with different radiological pictures. We evaluated the hypothesis to apply less restrictive radiological criteria to define PFI in patients with acute myeloid leukaemia (AML) submitted to chemotherapy. Overall, 73 consecutive episodes of pulmonary infiltrates associated to positive serum galactomannan test or fungal isolation or galactomannan detection from respiratory specimens were considered. CT scans acquired at the onset of symptoms (time‐0) and within 4 weeks (time‐1) were analysed to identify specific (group A) or aspecific radiological signs (group B). Pulmonary infiltrates fulfilled the EORTC‐MSG criteria in 49 patients (group A), whereas in 24 patients (group B) they did not reach the criteria due to aspecific CT findings at time‐0. Eleven of 21 (52.4%) patients of the group B evaluable for the evolution of the radiological findings fulfilled EORTC‐MSG criteria at time‐1. All the analysed clinical and mycological characteristics, response to antifungal therapy and survival were comparable in the two groups. Our study seems to confirm the possibility to extend the radiological suspicion of PFI to less restrictive chest CT findings when supported by microbiological criteria in high‐risk haematological patients.